Documenting Routinely What Matters to People: Standardized Headings for Health Records of Patients with Chronic Health Conditions - Prodinger, Birgit; Rastall, Paul; Kalra, Dipak; Wooldridge, Darren; Carpenter, Iain (Applied Clinical Informatics, 2018)
Objective Specifying the content in electronic health records (EHRs) through standardized headings based on international reference classifications will facilitate their semantic interoperability. The objective of this study was to specify potential chapter headings for EHRs aligned with the World Health Organization's (WHO) International Classification of Functioning, Disability, and Health (ICF) based on the perspectives of people living with chronic health conditions, carers, and professionals.Methods A multistage process was established including (1) a patient workshop, (2) an online survey of both patients and carers, and (3) an online consultation with patient and professional bodies. The ICF served as a starting point. Based on the first stage, a first draft of the headings was developed and further refined based on the feedback at each stage. We examined in a fourth step whether items from existing assessment tools support the operationalization of the identified headings. Therefore, we used the WHO Disability Assessment Schedule 2.0 (WHODAS2.0), a patient-reported instrument, and interRAI, a clinician-administered instrument.Results The first workshop was attended by eight people, the survey was completed by 250 persons, and the online consultation received detailed feedback by 18 professional bodies. This study resulted in 16 potential chapter headings for EHRs which capture aspects related to the body, such as emotions, motivation, sleep, and memory or thoughts, to being involved in social life, such as mobility, social activities, and finances, as well as to the care process, such as understanding of health issues and treatment or care priorities and goals. When using the WHODAS2.0 and interRAI together, they capture all except one of the proposed headings.Conclusion The identified headings provide a high level structure for the standardized recording, use, and sharing of information. Once implemented, these headings have the potential to facilitate the delivery of personalized care planning for patients with long-term health problems.
Keywords: patient's perspective; electronic health records; international classification of functioning; disability and health; semantic interoperability; chronic health conditions